The Events of Friday Ta'addud in the Text of Min al-Mihnah wa al-Musibah Ta'addud al-Jumu'at bi al-Ghasibah by Sayyid Uthman bin Yahya al-'Alawi: A Historical Review - Muhammad Zaelani; Muhammad Nida' Fadlan (LITTERATURA: Jurnal Bahasa dan Sastra, 2023)
The purpose of this study is to analyze the text Min al-Mihnah wa al-Musibah Ta'addud al-Jumu'at bi al-Ghasibah by Sayyid Usman bin Yahya al-‘Alawi, which can be a valuable resource for a broader audience, and to uncover its main ideas. This study adopts the intellectual social history approach and focuses on the manuscript as the primary data source. The findings of this study show that the manuscript contains a fatwa issued by Sayyid Usman bin Abdullah bin Aqil bin Yahya al-‘Alawi regarding the occurrence of ta'addud jum'at in Palembang, and it covers twelve topics. In the manuscript, Sayyid Usman argues that the Friday prayer performed in Palembang was invalid according to the Shafi'i school, and he also explains that the Shafi'i school permit ta'addud jum'at under two conditions: necessity and emergency. After reviewing the situation, he concluded that ta'addud jum'at was not valid in Palembang.